Utilisation of Snails for Wound Healing: A Review - Fadhilah, Diana; Santoso, Putra; Maliza, Rita (Universitas Gadjah Mada, 2024)
Snails exhibit remarkable adaptability, allowing them to flourish in diverse environmental conditions and resulting in thriving populations in specific regions. This abundance has led communities to harness snails for various purposes, including their use as animal feed, daily dietary source, and in traditional wound-healing practices with historical roots. The primary objective of this systematic review is to identify the snail species commonly employed in wound healing and evaluate the bioactivity of compounds derived from different snail species. This review was conducted using literature review method, drawing from international databases such as Scopus, and encompassed publications from 2013 to 2023. A total of 22 articles met the inclusion and exclusion criteria. Snail body parts that have been explored for wound-healing purposes include both the body and the shell, along with snail secretions, particularly their mucus. Various methods have been employed to extract mucus, involving manual stimulation of the snail's body, spraying with a saline solution (NaCl), application of electric shock, and the use of ozone gas through nebulisation. Prominent snail species found to be beneficial for wound healing include Achatina fulica, Helix aspersa, Eobania desertorum, Helix lucurus, Cornu bistrialis, Theba pisana, and Megalobulimus lopesi. These snail species demonstrate potential applications in the treatment of burns, excision wounds, incision wounds, and diabetic ulcers. Key compounds within snail secretions encompass mucopolysaccharides, polyphenols, peptides, and glycosaminoglycans. These compounds exert significant effects on haemostasis, inflammation control, cellular proliferation, and re-epithelialisation, significantly contributing to the wound healing process.